Fibre loop cavity ring-down spectroscopy for the sensitive and selective detection of minute sample volumes of liquid explosives - Rushworth, C; Vallance, C (2010)
Fibre loop cavity ring-down spectroscopy (FLCRDS) is a relatively new technique, which extends the more commonly used two-mirror cavity ring-down spectroscopy (CRDS) technique to measurements of optical absorption by minute liquid sample volumes. In this paper, loops of 50 μm-core-diameter multimode optical fibre were used to carry out both direct and evanescent wave FLCRDS measurements at 532 nm. The sensitivity of each technique was established by making measurements on a common dye, rhodamine 6G; detection limits were found to be in the micromolar range for aqueous rhodamine, in a sample volume of only a few picolitres. In this case, evanescent wave FLCRDS was found to be more sensitive than direct absorption. Functionalisation of the silica taper used for evanescent absorption measurements allows for binding measurements to be carried out. We report the results of preliminary proof-of-concept measurements on the binding of streptavidin to a biotinylated taper. © 2010 SPIE.